Edukasi Pencegahan Nyeri Bahu pada Pekerja Rumah Makan di Dapur Potre Koneng - Fitkiyah Nurul Khuzaimah; Nikmatur Rosidah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Introduction Shoulder pain is one of the most common complaints of Musculoskeletal Disorders (MSDs) experienced by workers due to non-ergonomic working postures, repetitive movements, and excessive workloads. This condition can reduce productivity and overall quality of life. Objective To increase restaurant workers’ knowledge about shoulder pain prevention through ergonomic education and simple stretching exercises that can be performed independently. Methods A descriptive observational study was conducted involving 20 kitchen workers at Potre Koneng Restaurant. The program consisted of permission procedures, workplace observation, questionnaire distribution, and health education using a leaflet. The educational material included the definition of shoulder pain, signs and symptoms, risk factors, preventive measures, and simple stretching techniques. Results The Form revealed that most workers experienced shoulder pain related to bending postures, lifting loads >5 kg, and limited rest breaks. Following the education session, participants demonstrated improved understanding of proper working posture and the importance of regular stretching, and expressed willingness to practice it during work breaks. Conclusion Ergonomic education and stretching exercises were effective in improving awareness of shoulder pain prevention among informal sector workers. Similar programs are recommended as promotive and preventive measures in high-risk workplaces.